2016
DOI: 10.1038/srep28039
|View full text |Cite
|
Sign up to set email alerts
|

Tumour endothelial cells in high metastatic tumours promote metastasis via epigenetic dysregulation of biglycan

Abstract: Tumour blood vessels are gateways for distant metastasis. Recent studies have revealed that tumour endothelial cells (TECs) demonstrate distinct phenotypes from their normal counterparts. We have demonstrated that features of TECs are different depending on tumour malignancy, suggesting that TECs communicate with surrounding tumour cells. However, the contribution of TECs to metastasis has not been elucidated. Here, we show that TECs actively promote tumour metastasis through a bidirectional interaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
186
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 121 publications
(194 citation statements)
references
References 49 publications
7
186
0
1
Order By: Relevance
“…Total RNA was extracted with an RNeasy Micro kit (Qiagen, Valencia, CA, USA). cDNA was synthesized using ReverTra‐Plus (Toyobo, Osaka, Japan), as previously described . Quantitative ‐PCR was performed with SsoFast™ EvaGreen® Supermix (Bio‐Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted with an RNeasy Micro kit (Qiagen, Valencia, CA, USA). cDNA was synthesized using ReverTra‐Plus (Toyobo, Osaka, Japan), as previously described . Quantitative ‐PCR was performed with SsoFast™ EvaGreen® Supermix (Bio‐Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…First, TECs usually have irregular shape and size [51]; second, TECs have distinct responsiveness to EGF, adrenomedullin and VEGF compared with normal endothelial cells [52][53][54]. Through a bidirectional interaction between tumor cells, TECs actively promote cancer metastasis [55]. Previous study also suggested that TECs isolated from highly metastatic tumors significantly enhanced the metastatic ability of weakly metastatic cancer cells in co-transplantation experiments [55].…”
Section: Cellular Components In the Tme That Suppress Tumor Progressionmentioning
confidence: 99%
“…Through a bidirectional interaction between tumor cells, TECs actively promote cancer metastasis [55]. Previous study also suggested that TECs isolated from highly metastatic tumors significantly enhanced the metastatic ability of weakly metastatic cancer cells in co-transplantation experiments [55]. Mechanistically, DNA demethylation in TECs causes upregulation and secretion of biglycan, which is a small leucine-rich repeat proteoglycan.…”
Section: Cellular Components In the Tme That Suppress Tumor Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether or not Biglycan produced by TEC can bind these factors is unknown and could provide grounds for further investigation to elucidate this matter. 91,92 …”
Section: The Role Of Vessel In Metastasismentioning
confidence: 99%